2005
DOI: 10.1098/rspb.2005.3125
|View full text |Cite
|
Sign up to set email alerts
|

Alternative life histories shape brain gene expression profiles in males of the same population

Abstract: Atlantic salmon (Salmo salar) undergo spectacular marine migrations before homing to spawn in natal rivers. However, males that grow fastest early in life can adopt an alternative 'sneaker' tactic by maturing earlier at greatly reduced size without leaving freshwater. While the ultimate evolutionary causes have been well studied, virtually nothing is known about the molecular bases of this developmental plasticity. We investigate the nature and extent of coordinated molecular changes that accompany such a fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
155
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(172 citation statements)
references
References 51 publications
17
155
0
Order By: Relevance
“…For example, Aubin-Horth et al (2005a) found that $15% of brain transcripts were significantly differently expressed in wild-caught salmon of two alternative life histories, and Aubin-Horth et al (2005b) found 10.5% were significantly differently expressed in a comparison of salmon of alternative life histories reared in either the wild or captivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Aubin-Horth et al (2005a) found that $15% of brain transcripts were significantly differently expressed in wild-caught salmon of two alternative life histories, and Aubin-Horth et al (2005b) found 10.5% were significantly differently expressed in a comparison of salmon of alternative life histories reared in either the wild or captivity.…”
Section: Discussionmentioning
confidence: 99%
“…Troponin is associated with actin and tropomyosin in the actin scaffold of muscle tissue (Roisen et al 1983). In neurons, these molecules are collectively associated with neural development and growth (Schevzov et al 1997;Aubin-Horth et al 2005a), thus potentially providing a link between troponin and behavioral differences between species pairs.…”
Section: Discussionmentioning
confidence: 99%
“…In the African cichlid, Astatotilapia burtoni, approximately 5 per cent of genes studied were differentially regulated in the brain according to male dominance phenotype (Renn et al 2008). Furthermore, distinct brain gene expression profiles were observed in male Atlantic salmon Salmo salar with alternative reproductive strategies (Aubin-Horth et al 2005a). Preliminary microarray analysis on the effects of social status on gene expression in rainbow trout Oncorhynchus mykiss observed more than 1000 gene differences in dominant, subdominant and subordinate fish including changes in stress-responsive genes (Sneddon et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, these parallel phenotypic changes may have the same underlying genetic basis [12 -17] or may involve different genetic changes that cause similar phenotypic responses [18,19]. While parallel adaptation may stem from novel mutations in the same gene or gene region, it is often attributed to concordant changes in the frequencies of existing alleles [14][15][16]20,21] or to parallel regulatory changes in gene expression [22,23]. However, the relative importance and frequency of these different underlying genomic responses to adaptive evolution in natural populations is largely unknown.…”
Section: Introductionmentioning
confidence: 99%